Carbon monoxide (CO) vertical profiles derived from joined TES and MLS measurements. Issue 18 (20th September 2013) - Luo, Ming; Read, William; Kulawik, Susan; Worden, John; Livesey, Nathaniel; Bowman, Kevin; Herman, Robert
Abstract [1] TES (Tropospheric Emission Spectrometer) nadir and MLS (Microwave Limb Sounder) limb measurements from the Aura satellite are used to jointly estimate an atmospheric carbon monoxide (CO) profile with extended vertical range compared to profiles retrieved from the individual measurement. We describe the algorithms, the processing procedures, the prototyping results, and the evaluations for this new joint product. TES and MLS "stand‐alone" CO profile retrievals are largely complementary, with TES being largely sensitive to lower to middle troposphere while MLS measures CO in the upper troposphere and above. We pair TES nadir and MLS limb tangent locations within 6–8 min and within 220 km. The paired radiance measurements of the two instruments in each location are optimally combined to retrieve a single CO profile along with other trace gases whose signal interferes with that from CO. This combined CO profile has a vertical resolution and vertical range that is an improvement over the two stand‐alone products, especially in the upper troposphere/lower stratosphere. For example, the degrees of freedom for signal (DOFS) between surface and 50 hPa for TES alone are < 2, and for the combined CO profiles are 2–4. This new Aura CO product will be made available to the public using TES V005 and MLS V003 processing results and will provide a unique data set for studying tropospheric transport of air pollutants and troposphere‐stratospheric exchange processes.